1988
DOI: 10.1136/bjsm.22.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a non-steroidal anti-inflammatory drug on delayed onset muscle soreness and indices of damage.

Abstract: Twenty untrained male volunteers were required to run downhill for 45 minutes on a motor driven treadmill to induce muscle soreness. The volunteers took diclofenac or placebo before and for 72 hours after two runs 10 weeks apart, in a randomised double blind crossover design. Subjective soreness was assessed before and at intervals up to 72 hours after each run; venous blood samples, collected at the same time intervals, were used to estimate serum activities of creatine kinase, lactate dehydrogenase and aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 19 publications
2
46
0
1
Order By: Relevance
“…Pomegranate polyphenols contain an abundance of antioxidant and anti-inflammatory properties [21]; thus, a potential mechanism for the improved strength recovery observed in PJC supplementation groups may be due to attenuated oxidative stress or inflammation at some point during the postexercise time period. However, it must be stated that this may not be the case, as studies that have investigated the effects of antioxidant or antiinflammatory supplementation on strength recovery after eccentric exercise have demonstrated equivocal findings [5][6][7][8][9][10][11][12][13][14][15]. Indeed, some studies have shown a beneficial effect of antioxidant supplementation at lower dosages [11,12], while, at higher dosages, others have shown no effect [7] or detrimental effects [9].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Pomegranate polyphenols contain an abundance of antioxidant and anti-inflammatory properties [21]; thus, a potential mechanism for the improved strength recovery observed in PJC supplementation groups may be due to attenuated oxidative stress or inflammation at some point during the postexercise time period. However, it must be stated that this may not be the case, as studies that have investigated the effects of antioxidant or antiinflammatory supplementation on strength recovery after eccentric exercise have demonstrated equivocal findings [5][6][7][8][9][10][11][12][13][14][15]. Indeed, some studies have shown a beneficial effect of antioxidant supplementation at lower dosages [11,12], while, at higher dosages, others have shown no effect [7] or detrimental effects [9].…”
Section: Discussionmentioning
confidence: 91%
“…Antioxidant and nonsteroidal antiinflammatory drugs (NSAIDs) have a negligible effect on strength recovery [5][6][7][8][9][10][11][12][13]. On the contrary, NSAID [10] and vitamin C [14,15] supplementation have been shown to alleviate muscle soreness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. "Bergablaufen" (Donnelly et al 1988, Donnelly et al 1990) und "Sprünge in die Tiefe" (Semark et al 1999 Belastung sogar verzögern könnten (Seidel et al 2012). …”
Section: Sedimentationsrateunclassified